Service quality delivery and its relationship on customers satisfaction in Maybank Tasek Gelugor / Suhana Md Desa - Md Desa, Suhana (2009)
The purpose of this study is to examine serviee quality delivery and its relationship on customer satisfaction in Maybank Tasek Gelugor. In order to generate more business and increase company's profit, the quality of service need to be improved therefore this research focused on the serviee quality and its impact on customer satisfaction. This research will help to identify the element of service quality that have directly influence the customer satisfaction towards serviee delivered by Maybank Tasek Gelugor Branch. Therefore, the study has been conducted in Maybank Tasek Gelugor branch. Pulau Pinang. Different background of respondents has been used in this study. Questionnaires in Bahasa Melavu and English has been distributed to 200 customers and the researcher managed to collect only 1 10 questionnaires from the respondents. The respondents were asked to answer on the element of service quality in order to determine their level of satisfaction towards serviee delivered by Maybank Tasek Gelugor branch. Hypotheses of the study were tested using SPSS tools. Overall result of the findings indicates that the independent variable and dependent were found to be excellent and the study supported the hypotheses of the study and were found to be significantly related to customer satisfaction. The study highlights implications for marketers in banking industry for improvement in delivery of service quality.